2020
DOI: 10.1111/eip.13050
|View full text |Cite
|
Sign up to set email alerts
|

The Recovering Quality of Life 10‐item (ReQoL‐10) scale in a first‐episode psychosis population: Validation and implications for patient‐reported outcome measures (PROMs)

Abstract: Aim This study aimed to examine the psychometric performance of the Recovering Quality of Life scale 10‐item version (ReQoL‐10) using a sample from a Singapore first‐episode psychosis intervention program, to explore its clinical and sociodemographic correlates, and to discuss its utility as a patient‐reported outcome measure (PROM). Methods Sociodemographic data, duration of untreated psychosis (DUP), and diagnosis were collected from 300 participants. Clinical data, which included baseline and current scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…To address the issue of non-normal data, the robust distribution free weighted least squares (WLSMV) estimator was used (Ferrando and Lorenzo-Seva, 2000;Markon, 2019). Several a priori hypotheses about the relationship between the ReQoL-TC and the other HRQoL and mental health instruments were formulated to test the convergent validity of the ReQoL-TC (Keetharuth et al, 2018b;Chua et al, 2020;van Aken et al, 2020) (specific hypotheses are presented in Supplementary Table 1). The strength of the correlation was estimated using Pearson's correlation coefficient (r), where r ≥ 0.55 were interpreted as adequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the issue of non-normal data, the robust distribution free weighted least squares (WLSMV) estimator was used (Ferrando and Lorenzo-Seva, 2000;Markon, 2019). Several a priori hypotheses about the relationship between the ReQoL-TC and the other HRQoL and mental health instruments were formulated to test the convergent validity of the ReQoL-TC (Keetharuth et al, 2018b;Chua et al, 2020;van Aken et al, 2020) (specific hypotheses are presented in Supplementary Table 1). The strength of the correlation was estimated using Pearson's correlation coefficient (r), where r ≥ 0.55 were interpreted as adequate.…”
Section: Discussionmentioning
confidence: 99%
“…A bifactor model of the ReQoL comprising a global factor and two local factors of negative and positive affects was reported by the developers ( Keetharuth et al, 2018a ). ReQoL has been translated into different languages and shown good reliability and validity ( Keetharuth et al, 2018b ; Chua et al, 2020 ; van Aken et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ReQoL-10 was reliable in a sample with patients with psychosis and the ReQoL measures showed good convergent and known-group validity [17]. In a firstepisode psychosis population in Singapore, ReQoL-10 was found to have good internal consistency and adequate construct validity [30].…”
Section: Introductionmentioning
confidence: 93%
“…So far, the psychometric properties of the ReQoL measures have been assessed in patients with anxiety and depression in the United Kingdom [29], in patients with psychosis in the Netherlands [17] and Singapore [30], in the general population in the United Kingdom [15] and Hong Kong [25] as well as in a convenience sample in the Netherlands [17]. For the patient populations, the ReQoL measures showed good internal consistency and better responsiveness and construct validity compared with the EQ-5D-5L in patients with depression, but not in patients with anxiety [29,30]. Furthermore, the ReQoL-10 was reliable in a sample with patients with psychosis and the ReQoL measures showed good convergent and known-group validity [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literature examining the personal recovery approach also began to emerge in 2019 to 2020, exploring the lived experiences of people with psychosis 16 and hoarding, 17 evaluating peer support services, 18 and testing various recovery-oriented measurement tools. 19,20 It may be observed that the latter half of the 2010s was an indicator of an impending paradigm shift and the beginning of more personal recovery-oriented perspectives being seeded across the mental healthcare landscape in Singapore. Beyond these developments, there have not been any major/sustained efforts to introduce personal recovery principles into existing mental health services and research agendas.…”
mentioning
confidence: 99%